Genetic improvement of silage maize: predicting genetic gain using selection indexes and best linear unbiased prediction - Crevelari, Jocarla; Pereira, Messias; Azevedo, Flávio Henrique; Vieira, Ricardo Augusto (Revista Ciência Agronômica, 2019)
The objective of this study was to evaluate four selection indexes and best linear unbiased prediction (BLUP) for predicting genetic gain in maize hybrids used for silage. The genetic gain was compared between four selection indexes and BLUP. Nineteen topcross hybrids and five controls were evaluated using a completely randomized block design with four replicates in two areas located in Campos dos Goytacazes and Itaocara, Rio de Janeiro, Brazil, in the growing season 2013-2014. Plant height, first ear height, average stem diameter, grain yield at the silage stage, and green mass yield were evaluated. The genetic gain was predicted using the selection indexes proposed by Pesek and Baker, Smith and Hazel, Mulamba and Mock, Willians, and BLUP. The index of Mulamba and Mock provided higher gain estimates for selecting hybrids. BLUP was efficient and selected hybrids with higher performance than hybrids obtained using the four selection indexes. Hybrids UENF-2205, UENF-2208, UENF-2209, and UENF-2210 presented better performance, indicating the high potential of these dent hybrids for silage production in the north and northwest regions of Rio de Janeiro.